Nanoparticle Assembly and Gelatin Binding Mediated by Triple Helical Collagen Mimetic Peptide - San, Boi Hoa (ACS Appl Mater Interfaces, 2016)
Peptide-conjugated nanoparticles (NPs) have promising potential for applications in biosensing, diagnosis, and therapeutics because of their appropriate size, unique self-assembly, and specific substrate-binding properties. However, controlled assembly and selective target binding are difficult to achieve with simple peptides on NP surfaces because high surface energy makes NPs prone to self-aggregate and adhere nonspecifically. Here, we report the self-assembly and gelatin binding properties of collagen mimetic peptide (CMP) conjugated gold NPs (CMP-NPs). We show that the orientation of CMPs displayed on the NP surface can control NP assembly either by promoting or hindering triple helical folding between CMPs of neighboring NPs. We also show that CMP-NPs can specifically bind to denatured collagen by forming triple-helical hybrids between denatured collagen strands and CMPs, demonstrating their potential use for detection and selective removal of gelatin from protein mixtures. CMP conjugated NPs offer a simple and effective method for NP assembly and for targeting denatured collagens with high specificity. Therefore, they may lead to new types of functional nanomaterials for detection and study of denatured collagen associated with diseases characterized by high levels of collagen degradation.